PROTOTYPING AN IOT-BASED SMART FACTORY SYSTEM FOR LEAN TPS EDUCATION AND SME APPLICATIONS - Andi Nurwahidah; Ramadhan, Della Ginza; Lutfi; Azis, Muhammad Fadli; Indah, Andi Besse Riyani (JEMIS (Journal of Engineering & Management in Industrial System), 2025)
The Production System Laboratory hosts hands-on TPS sessions. Yet, despite efforts to digitize the session experience, until they are recorded it's impossible for us to view adequately what's occurring at workstations.On the other hand, this research project uses the smart factory prototype which is based on the Internet of Things (IoT) to realize the sights and control of production processes. Using MQTT, Node-RED and MySQL, real time production data is captured and can be displayed in this prototype system.Tests of this system were carried out in four TPS work stations. These results show that on average it took 3000 ms to process the data, with an accuracy rate of 99% for recorded production data, and less than one second delay when data was visualized. Moreover, the introduction of this system turned around accrued writing mistakes on WIP tracking by 99 % and shortened it time for recording by up to 90%. The final overall results indicated that the system improved lean-based lab components operations substantially and has potential to be used by small to medium enterprise enterprises (SMEs) looking for economical ways to increase production and process visualization.